Cefr-Based Mahara Al-Kitabah Competencis in Class V Textbooks at Madrasah Tsanawiyah Level in Indonesia - Kabul Hidayah (Edumaspul: Jurnal Pendidikan, 2023)
In Indonesia, the achievement standards for learning Arabic in Maharah Al-Kitabah are core competencies and basic competencies in each sub- and sub-sab in the teaching materials used, while in international forums the reference used is the Common European Framework of Reference for Language (CEFR). Competency standards are divided into several levels and can be modified according to the level of ability of students. In addition, the CEFR is also equipped with an assessment instrument to measure the development of students' abilities in all language skills, namely maharah istima', kalam, qiroah, kitabah. This study aims to examine CEFR-based maharah al-kitabah competencies in Arabic textbooks for class VII at the Tsanawiyah Madrasah level. This research is a qualitative research using a descriptive analysis approach that uses documentation to collect data. The results of this study are: the achievement of maharah al-kitabah class VII at the madrasah tsanawiyah level is at level B1.